“As história são boa. As pessoas, maravilhosa": análise da variação da concordância verbal e nominal na zona rural de Santa Leopoldina/ES - Lopes, Lays de Oliveira Joel (2020)
Based on the Variationist Sociolinguistics, systematized and disseminated by Labov (2008 [1972], 2001), this research analyzes the phenomena of third person verbal agreement and nominal number agreement in the noun phrase, from a sample composed of 44 int